Evaluating the Effectiveness of a Structured Self-Care Intervention in Improving Diabetes Management in Urban and Rural Populations - Gupta, Shikha; Khan, Azra; Singh, Ranjana (Journal of Neonatal Surgery, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a growing health challenge in both urban and rural India. Effective self-care is essential for preventing complications and premature mortality, yet adherence remains suboptimal. This study evaluates the effectiveness of a structured, theory-driven self-care intervention in improving diabetes management among adults with T2DM in urban and rural settings. Methods: A sequential mixed-methods design was used. The formative phase included qualitative research to identify barriers and facilitators to self-care in both urban and rural populations. Insights informed the development of a structured intervention package, which was evaluated using a quasi-experimental design. Participants (n=440; 220 intervention, 220 control) were recruited from urban and rural communities in Greater Noida India. Data on self-care behaviors and clinical outcomes were collected at baseline, 6 months, and 12 months. Difference-in-difference analysis assessed intervention effectiveness. Results: The intervention significantly improved self-care behaviors (medication adherence, diet, physical activity, blood glucose monitoring, foot care) and clinical outcomes (HbA1c, fasting blood sugar, BMI) in both urban and rural participants compared to controls. Urban participants showed slightly greater improvements in glycemic control, while rural participants benefited from tailored support strategies. Conclusion: A structured self-care intervention, grounded in behavioral change theory, can enhance diabetes management in both urban and rural populations. Integration into existing healthcare systems is recommended for broader impact.